Role of Information and Communication Technologies (ICTs) in agriculture trade’s information - KUMAR, RUPENDER; CHAHAL, PARDEEP; MUKTESHAWAR, R; MEENA, DEVENDRA KUMAR; KUMAR, SANJEEV (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out in four districts of Haryana during 2017. Farmers use ICTs for various activities such as marketing, marketing price, time of market inflow, quality parameters that affect price, marketing procedure and other facilities available at marketplace. The results indicate that majority of the farmers use ICTs for the purpose of information of weather forecasting, crops related government policies, credit/loan facilities for crops cultivation, insurance of crop and subsidies for crop cultivation. The variables: education, socio-economic status, land holding, extension contact, mass media exposure, scientific orientation, economic motivation and risk orientation exhibited significantly positive correlation with marketing of agricultural produce, whereas age was significantly negatively correlated with marketing. The regression analysis shows significantly positive impact of education, socio-economic status, land holding, extension contact, mass media exposure, economic motivation and risk orientation on agricultural produce marketing, whereas, age, scientific orientation and irrigation facilities exhibited significantly negative impact on marketing.